O MAL: DESCONCERTO DA NATUREZA HUMANA… UMA LEITURA DE “O AMOR EM LOBITO BAY” DE LÍDIA JORGE - TORRÃO, Nazaré (Studia Universitatis Babeș-Bolyai Philologia, 2019)
Evil: The Disarray of Human Nature... A Reading of “O Amor em Lobito Bay” by Lídia Jorge. Lídia Jorge is a writer whose work questions and probes into the Portuguese society when it comes both to some aspects of its history, the dictatorship of the New State, the colonial war or the Carnation Revolution of 1974 as specific components of the Portuguese culture and society (the profound social change the revolution has entailed, the national identity), and to others that are common to any contemporary Western society: the female condition, discrimination against the other, violence and so on. In this study I intend to analyse her collection of short stories O Amor em Lobito Bay (Love in Lobito Bay) (2016). In the nine short texts that make up the book we are told about stories happening around the world like nine mirrors reflecting different facets of the violent contemporary society. In them, the author reveals the different forms evil can take so as to show us the pernicious stages that could lead us to accept it as inevitable or justified. To the anxiety caused by all these stories due to the difficulty of explaining the origin of evil, an answer is offered (by means of another question) which does not belong to the order of reason, but rather to that of action: what is there to do against evil? The first step is to admit one’s guilt, and it is one of the reasons why the locutory mode chosen for the narrative is crucial in the process leading to the characters’ awareness – their admission of guilt – the same as literary communication can be to the author and her readers. “Writing is a way of resisting”, Lídia Jorge said at her book launch. This study will try to analyse this issue in four of the short stories, taking into account the notions of evil (according to the theories propounded by Ricoeur, Kant and Arendt), of the contemporary (Agamben) and of the in-between (Sibony). REZUMAT. Răul: dezordinea naturii umane... O lectură a volumului “O Amor em Lobito Bay” (“Iubire la Lobito Bay”) de Lídia Jorge. Lídia Jorge este o scriitoare a cărei operă examinează și interoghează societatea portugheză atât cu privire la unele aspecte ale istoriei sale, ale dictaturii Noului Stat, ale războiului colonial și ale Revoluției Garoafelor din 1974 ca elemente specifice culturii și societății portugheze (precum schimbarea socială profundă determinată de revoluție, identitatea națională), cât și cu privire la alte aspecte comune oricărei societăți occidentale contemporane: condiția femeii, discriminarea celuilalt, violența etc. În studiul de față doresc să analizez antologia sa de nuvele O Amor em Lobito Bay (Iubire la Lobito Bay) (2016). În cele nouă texte ce compun volumul ni se povestesc întâmplări ce au loc peste tot în lume, ca nouă oglinzi ce reflectă diverse fațete ale violentei societăți contemporane. Autoarea dezvăluie aici variatele forme pe care le poate lua răul, pentru a dezvălui etapele periculoase ce ne pot determina să-l acceptăm ca inevitabil sau justificat. Anxietății provocate de aceste povestiri, cauzată de dificultatea explicării originii răului, autoarea îi oferă o soluție (cu ajutorul altei întrebări), nu de ordinul rațiunii, ci de ordinul acțiunii: ce se poate face împotriva răului ? Primul pas este recunoașterea vinovăției și acesta e unul dintre motivele pentru care forma aleasă pentru discursul narativ este esențială în procesul ce determină conștientizarea personajelor – recunoașterea culpabilității de către acestea – la fel cum comunicarea literară însăși poate fi crucială pentru autoare și cititorii săi. “Scrisul e o formă de rezistență”, spunea Lídia Jorge la prezentarea cărții. Acest articol va încerca să analizeze această problemă în patru dintre nuvele, cu ajutorul noțiunilor de rău (din teoriile propuse de Ricoeur, Kant și Arendt), contemporaneitate (Agamben) și între (Sibony). Cuvinte cheie: Lídia Jorge, O Amor em Lobito Bay (Iubire la Lobito Bay), rău, Ricoeur, Kant, Arendt, Sibony.